The Implementation of Digital Storytelling to Enhance Early Childhood Learning Experiences - Hardini, Marviola; Yusup, Muhamad; Kareem, Yasir Mustafa; Astuti, Eka Dian (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2026)
This study examines how digital storytelling can enhance early childhood learning experiences in preschool settings, in response to the growing integration of technology in education and the need to ensure its alignment with develop-mentally appropriate practices. The objective of this research is to explore how the implementation of digital storytelling influences children’s cognitive engagement, social interaction, and creative expression. Employing a qualitative de- scriptive approach, the study involves 18 children aged 4-6 years in a preschool setting and utilizes classroom observations, structured interviews with teachers, and documentation of learning activities to analyze the implementation process and its pedagogical impact. The findings indicate a tendency toward improved attention span, vocabulary development, and collaborative behavior, as well as enhanced imagination and emotional expression during digital storytelling ses- sions. Teachers reported that digital tools contributed to more interactive and adaptive learning environments, enabling children to connect personal experi- ences with narrative content in meaningful ways. The study concludes that integrating digital storytelling in early childhood education holds strong poten- tial as a developmentally aligned instructional strategy, supporting both child independence and holistic development. It further highlights the importance of thoughtful technological integration in preschool classrooms as a bridge be- tween modern educational innovation and child-centered learning philosophies.